Defining a Health Benefits Package: What Are the Necessary Processes?. Issue 1 (2nd January 2016) - Glassman, Amanda; Giedion, Ursula; Sakuma, Yuna; Smith, Peter C.
Abstract : Abstract— There is immense interest worldwide in the notion of universal health coverage (UHC). A major policy focus in moving toward UHC has been on the key policy question: what services should be made available and under what conditions? In this article we are concerned with how a feasible set of UHC services can be explicitly defined to create what is commonly known as a "health benefits package" (HBP), a set of services that can be feasibly financed and provided under the actual circumstances in which a given country finds itself. We explain why an explicit statement of the HBP is important and then describe a framework that includes ten core elements that are indispensable if a coherent and sustainable process for setting the HBP is to be established.